Boronic acid inhibitors of the class A β-lactamase KPC-2. Issue 11 (15th July 2018) - Zhou, Jingyuan; Stapleton, Paul; Haider, Shozeb; Healy, Jess
Graphical abstract: Abstract: The rapid rise of antimicrobial resistance is one of the greatest challenges currently facing medical science. The most common cause of resistance to β-lactam antibiotics is the expression of β-lactamase enzymes, such as KPC-2. As such the development of novel inhibitors of KPC-2 and related enzymes is of the upmost importance. We report the design and synthesis of novel boronic acid transition state analogs containing a 1, 4-substituted 1, 2, 3-triazole linker based on the known inhibitor 3-nitrophenyl boronic acid and demonstrate that they are promising scaffolds for the development inhibitors of KPC-2 with the ability to recover sensitivity to the antibiotic cefotaxime.